Harnessing Platform Envelopment in the Digital World. (18th April 2020) - Condorelli, Daniele; Padilla, Jorge
Abstract: We revisit the economics of "platform envelopment strategies, " whereby a dominant platform (the enveloper) operating in a multi-sided market (the origin market) enters a second multi-sided market (the target market) by leveraging the data obtained from its shared user relationships. In particular, we analyze the logic and effects of "privacy policy tying, " a strategy whereby the enveloper requests consumers to grant their consent to combining their data in both origin and target markets. This may allow the enveloper to fund the services offered to all sides of the target market by monetizing data in the origin market, monopolize the target market, and entrench its dominant position in the origin market. We conclude by considering a range of possible policy interventions that may serve to limit such potential anticompetitive effects, while preserving the efficiencies generated by conglomerate platforms.